Pricing Policy for Supply of Bamboos to Paper Industries and Weaker Sections in Andhra Pradesh - Sarangi, P. K. (Indian Forester, 2008)
The forest resources of all the states are dwindling and the supply of forest produce to forest based industries has to be re-examined. In this context the supply rates of Bamboo Industrial Cuts to various paper mills of Andhra Pradesh and adjoining states of A.P. have been analyzed. The existence of "A.P. Forest Produce (Fixation of Selling Prices) Rules, 1991" in the state has significantly facilitated the "price fixation policy" based on the demand and supply in the market, without affecting the sustainability of our forests. Similarly, the supply of long bamboos to the weaker sections of the society (’Burrods’) has to be met at reasonable price. Hence, there is a need to rationalize the prices of supply of Bamboo Industrial Cuts to paper mills in other states, so as to maximize the revenue, as followed in Andhra Pradesh. Even in the state, there is a need to re-examine the extraction and sale of 3rd class long bamboos, as the rate fetched in open auction for the 3rd class bamboo is much less compared to the prices obtained for the Bamboo Industrial Cuts.